Archaea: A Gold Mine for Topoisomerase Diversity - Garnier, Florence; Couturier, Mohea; Débat, Hélène; Nadal, Marc (Frontiers in Microbiology, 2021)
The control of DNA topology is a prerequisite for all the DNA transactions such as DNA replication, repair, recombination, and transcription. This global control is carried out by a class of essential enzymes, named DNA-topoisomerases, that are mandatory for the genome stability. Despite their very different life styles, Archaea share a quasi homogeneous topoisomerases content except thermophilic organisms that possess at least one reverse gyrase that is considered a marker of the thermophily. Here, we review the content of these essential enzymes within all the archaeal diversity based on the available genomic data, and we discuss their putative roles, in particular in the processes involved in both the archaeal adaptation and the preservation of the genome stability. This review is dedicated to the memory of Maria Ciaramella who largely contributed to the understanding of the DNA-topoisomerases and the DNA repair field in Archaea.